Implementation of an HDR Tone Mapping Operator Based on Human Perception - Yannick Rietz (Hochschule für angewandte Wissenschaften Hamburg, 2017)
The goal of this bachelor thesis is the implementation of a specific HDR tone mapping operator for a real-time 3D game engine. Particular emphasis is placed on simulation of detail visibility. The text describes the relevant characteristics of the human visual system. It details the mode of operation of the operator and includes a walkthough of the specifics of the new implementation.